MoS2/graphdiyne nanotube/MXene 3D-interconnected ternary aerogel: A high-performance electrocatalyst for hydrogen evolution reaction - Samawi, Khalida Abaid; Abdulrazzaq, Shaymaa Jabbar; Zorah, Mohammed; Al-Bahrani, Mohammed; Mahmoud, HassabAlla M.A.; Abdulkareem-Alsultan, G.; Taki, Anmar Ghanim; Nassar, Maadh Fawzi (Academic Press, 2024)
MoS2 is a promising challenger to Pt for the HER, but we must make it more durable before it can take over the hydrogen production scene. This work fabricated and evaluated a hybrid structure of MXene-graphydine nanotube-MoS2 (MGMX) aerogel toward HER. It showed efficient and stable activity H2 evolution with ƞ10 = 109 mV vs RHE and a Tafel slope of 55 mVdec−1. The catalytic performance results from a synergistic interplay between increased exposed active sites and improved charge transfer within the catalyst. The two-dimensional (2D) islands of double-phase MoS2 are directly deposited onto graphdiyne nanotubes (GDNTs) surface, creating a structurally interesting material with interconnected components. The unique combination of sp and sp2 carbon atoms in the graphdiyne (GDY) makes it an ideal support for catalyst material. The combination of high edge density in metallic MoS2, a conducting MXene framework, and the bridging structure of GDNT significantly enhance the overall HER performance of the ternary aerogel structure.